Integration of Palembang LRT in the E-Module for Alternating Current Electricity STEM: A Study of Validity, Practicality, and Effectiveness - Devi Permata Sari; Ketang Wiyono; Sardianto Markos Siahaan (Postgraduate, University of Mataram, 2025)
This study aims to develop a STEM-based alternating current electricity e-module integrated with Palembang local wisdom, and to test its validity, practicality, and effectiveness. The development method used is the 4D model, which includes the defining, designing, developing, and disseminating stages. Validation activities involved nine experts, while the trial was carried out in two stages, namely a limited trial with nine students and a broad trial with eighteen students of grade XII. The validation results, all of which were classified as valid to very valid. In the practicality test, the ease of use aspect reached a very practical category, as did the display design and the presentation of material and benefits, all of which were in the very practical category. The highest improvement was obtained in the elaboration indicator, as the e-module provided open-ended problems that encouraged students to use imagination and reasoning in solving them. At the dissemination stage, the developed product was distributed through Google Sites so that it could be easily accessed by students and teachers. Thus, the STEM-based e-module is declared valid, practical, and effective for use as innovative learning media relevant to both the Alternating Current Electricity topic and the context of the Palembang LRT.